Cognitive Inertia in a Turbulent Market: the Case of UK Residential Estate Agents - Hodgkinson, Gerard P. (Journal of Management Studies, 1997)
Recently, a number of researchers seeking to develop cognitive approaches for understanding processes associated with the development and implementation of competitive positioning strategies have drawn attention to the notion of ‘cognitive inertia’. Once established, there is a danger that actors may become overly dependent on their mental models of competitive space, to the extent that they fail to notice changes in the material conditions of their business environment, until these changes have become so widespread, or significant in other ways, that their organization's capacity for successful adaptation has been seriously undermined. While there have been several anecdotal accounts of cognitive inertia reported in the literature, and a number of researchers have explored processes of cognitive change in organizations more generally, to date there have been virtually no studies published which have investigated this phenomenon specifically within the domain of competitor assessment. This paper reports one such investigation, a longitudinal field study which explored the extent to which actors' mental models of competitive space in the UK residential estate agency (real estate) industry, an industry characterized by high volatility in recent years, remained stable or changed over time. An initial sample of 208 respondents from 58 firms completed detailed questionnaires at the onset of the recent recession in the UK property market. The questionnaires were designed to elicit the respondents' perceptions of their own organization and various competitors on a number of key dimensions. A sub‐sample of 114 respondents from 41 firms returned a further set of completed questionnaires, 12 to 18 months later, when the recession had become deeply established. The findings are entirely consistent with the cognitive inertia hypothesis. The results indicate that the respondents' individual and collective cognitions remained highly stable, despite a significant down‐turn in the property market from T1 to T2.